Factors influencing fistula formation following perianal abscess treatment - Huseynov, Amil; Kuşlu Çiçek, Sevim Nuran (The European Research Journal, 2025)
Objectives: Perianal abscesses are frequently encountered in clinical practice and are primarily attributed to a cryptoglandular origin. Despite prompt incision and drainage, a subset of patients still develop anal fistulas. This study aims to identify risk factors associated with fistula formation after perianal abscess management. Methods: A total of 145 patients (64 females, 81 males) with perianal abscess were retrospectively reviewed between 2020 and 2024. All underwent urgent incision and drainage under anesthesia. Demographic characteristics, comorbidities, type of surgical intervention, and postoperative outcomes were analyzed. Postoperative complications were assessed at both early (≤30 days) and late (>30 days) time points. Univariate and logistic regression analyses were conducted to determine independent predictors of fistula formation. Results: The median patient age was 42 years (IQR: 35-50), and 37.9% had at least one comorbidity (17.2% diabetes mellitus, 13.8% hypertension). Intraoperative fistulas were identified in 37.9% of cases and managed via fistulotomy or seton placement when feasible. Early postoperative complications occurred in 24.1% of patients, most of which were minor. Over a median follow-up of 7 months (IQR: 4-12), abscess recurrence was observed in 6.9% and new-onset fistula in 14.5%. Comorbidities such as diabetes mellitus were associated with a higher likelihood of fistula formation. Anal incontinence was documented in 2.8% of patients, most cases resolving spontaneously or with conservative measures. Conclusions: Although urgent incision and drainage generally yields favorable early outcomes, a notable proportion of patients develop late complications, particularly fistula formation. Close follow-up and tailored surgical strategies, including fistulotomy or seton placement when indicated, may help reduce morbidity. Prospective and multicenter studies with extended follow-up are warranted to further refine treatment protocols and identify high-risk individuals.